2011
DOI: 10.4995/wrs.2011.849
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of decreasing stocking densities in broiler rabbit production based on Belgian farm data

Abstract: AbstrAct:Stocking density is a prominent issue in public debates on farm animal welfare. Public perceptions and economic impact of reduced stocking density should be considered, along with effects on animal performances and welfare. In this paper, experimental data and accountancy data based on 15 Belgian farms were combined to calculate the financial impact of different stocking densities on broiler rabbit farm profitability. Using the partial budget technique, only those elements that change with stocking de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Ainsi, un engraissement conduit en cages individuelles ou de deux (système Italien) permettrait d'améliorer l'ICg de 5 à 10 %, comparativement à des cages de 6 à 8 lapereaux (Trocino et al, 2015). En cuniculture conventionnelle, les variations de densité entre fermes, habituellement autour de 15 lapins/m², peuvent expliquer de 5 à 6 % des variations d'ICg (Verspecht et al, 2011). En revanche, dans le cas d'un engraissement en parcs, ou en extérieur, ou au sol, on doit s'attendre à une détérioration sensible de l'ICg.…”
Section: De Nombreuses Données D'efficacitéunclassified
“…Ainsi, un engraissement conduit en cages individuelles ou de deux (système Italien) permettrait d'améliorer l'ICg de 5 à 10 %, comparativement à des cages de 6 à 8 lapereaux (Trocino et al, 2015). En cuniculture conventionnelle, les variations de densité entre fermes, habituellement autour de 15 lapins/m², peuvent expliquer de 5 à 6 % des variations d'ICg (Verspecht et al, 2011). En revanche, dans le cas d'un engraissement en parcs, ou en extérieur, ou au sol, on doit s'attendre à une détérioration sensible de l'ICg.…”
Section: De Nombreuses Données D'efficacitéunclassified
“…It has been stated that a stocking density lower than 16 rabbits/m 2 had no effect on the growth performance of growing rabbits (e.g., Trocino et al, 2004;Szendrő et al, 2009). Verspecht et al (2011) reported that feed conversion and feed intake were found to increase slightly with decreasing stocking density. Similarly, Xiccato et al (2013) observed that the slaughter and carcass traits and meat quality were weakly affected by the housing system.…”
mentioning
confidence: 99%